Design Of Tracer Using Microsoft Access Unit In Medical Record Primary Health In Padang - Deni Maisa Putra; Alfauzain Alfauzain (International Journal of Engineering, Science and Information Technology, 2021)
Microsoft Access (also known as Access) is an application used to process databases. The implementation of storage at the Primary Health Center is still manual if the patient's medical record file is not found on the storage shelf, the officer will make a temporary file which will cause the accumulation of files on the shelf. There is still a misplaced medical record file (Missfile) due to the absence of a tracer being stored as a control for releasing medical record files and borrowing medical record files. The purpose of this research is how to design a tracer using Microsoft Access in the medical record unit at Primary Health Center, Padang. This research is about designing a tracer in the medical record unit at Primary Health Center in Padang. This type of research is Research and Development, conducting in-depth interviews, observation, and testing at the storage area and interviews with 1 head of administration, 1 head of medical records, and 2 storage officers. This research was conducted from 25 July to 2 August 2019 at Padang Primary Health Center. Based on the research results, it was found that the identification of tracer data elements in a computerized manner was more complete in implementing the application by developing the UML (Unified Modeling Language) method, namely by using use case diagrams and activity diagrams, as well as data flow diagrams. Efficiency is obtained by means of manually, 1 and computerized 3.5 so that the tracer efficiency is more computerized while the effectiveness is in accordance with what the officers expect. The conclusion in this study found that the officers were satisfied and the application was as expected because it was easy to use. Judging from the test results, this tracer application can be used, seen from the expectations and satisfaction of the officers, the data is appropriate and can improve performance, effectiveness, and efficiency in service. Therefore, the researchers hope that this application can be implemented in services and developed again in the future.